Bicycle helmet use among American children, 1994. Issue 4 (December 1996) - Sacks, J. J.; Kresnow, M.; Houston, B.; Russell, J.
Abstract : OBJECTIVE: To estimate ownership and use of bicycle helmets among children in the US in 1994. METHODS: As part of a 1994 national telephone survey of 5, 238 randomly dialed households, adult respondents reported data on bicycle helmet ownership and helmet use among 1, 645 child bicyclists. Data were weighted to provide national estimates. RESULTS: It is estimated that 72.7% of children 5-14 year olds ride bicycles, that is, 27.7 million child bicyclists. Of the bicyclists, 50.2% have a helmet and 25.0% reportedly always wore their helmet when cycling. Reported helmet ownership and use increased with income and educational level and decreased with age. Among regions of the US, those with the highest proportion of states with helmet use laws in 1994 also had the highest proportion of helmet use among children. Among child bicyclists who had been seen by a health care provider in the preceding 12 months, 43.9% of those counseled to wear a bicycle helmet were reported to comply compared with 19.1% of those seen by a provider but not so counseled (p < 0.001). CONCLUSIONS: To meet the year 2000 objective of 50% of bicyclists wearing helmets, use among American children will have to double. Concerted and increased efforts to promote the wearing of bicycle helmets are necessary.